Application System for Tracking Training and Physical Condition of Student Cadets in the Student Cadet Corps Regiment - Nurdiansyah, Agung; Putri Amalia Nugroho, Anatasya; Faza Hafasi, Ibran; Davin Rizqullah, Ruvian; Ahmad Firdaus, Eryan (Jurnal ICT : Information and Communication Technologies, 2026)
Monitoring physical condition and training activities is an important aspect in the development of student cadets within the Student Cadet Corps Regiment. However, the monitoring process that is still conducted manually reduces the effectiveness of tracking training compliance and the physical development of cadets. This study aims to design and develop a web-based application system for tracking the training activities and physical conditions of student cadets to support structured recording, monitoring, and evaluation of physical fitness. The system development method used in this research is Rapid Application Development (RAD), which emphasizes rapid prototyping and iterative improvements based on user feedback. The system was developed using the CodeIgniter framework for backend development, Bootstrap for frontend design, and MySQL as the database management system. The application enables cadets to record running activities and physical condition data such as height and weight, which are then calculated using the Body Mass Index (BMI) method. The data are stored in the database and visualized through graphical progress reports to facilitate monitoring of training outcomes. In addition, the system provides an administrative dashboard that allows regiment officials to centrally monitor the physical condition and training compliance of cadets. The results show that the developed system can improve the effectiveness and efficiency of training monitoring compared to the previously used manual method.